Mothers' preferences regarding new combination vaccines for their children in Japan, 2014 - Aiko Shono; Masahide Kondo (Taylor & Francis Group, 2017)
A number of new vaccines to prevent childhood diseases have been introduced globally over the last few decades. Only four combination vaccines are currently available in Japan, DTaP/sIPV, DTaP, DT, and MR, leading to complex infant vaccine scheduling. This study aims to investigate mothers' preferences with respect to combination vaccines for their children, should new combination vaccines become available that have not yet been launched in Japan or that will be developed in the future. We conducted a web-based, cross-sectional survey of 1,243 mothers who had at least one child between 2 months and 3 y of age. Mothers were recruited from an online survey panel of registered users. Their preferences were elicited using discrete choice experiments, the analyzed main effects model, and interactions using a mixed logit model. Mothers showed a preference for vaccines that prevented multiple diseases, had fewer injections per doctor visit, lower price, and lower risk of adverse events. Respondents valued a reduced risk of adverse events the most among all attributes in this study. The estimated monetary value of the willingness to pay for a 1% reduction in the risk of adverse events was ¥ 92,557 ($ 907). Therefore, if new combination vaccines are introduced, the risk of adverse events after vaccination is an especially important factor for mothers. While the safety of the vaccines themselves is required, health professionals should also inform mothers about the benefits and risks of vaccination, to allay mothers' concerns about vaccine safety.